2018
DOI: 10.1007/s11071-018-4174-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the dynamical behavior of a dual-frequency parametric amplifier with quadratic and cubic nonlinearities

Abstract: The paper describes a novel parametric excitation scheme that acts as a tunable amplifier by controlling two pumping signals and two nonlinear feedback terms. By modulating the stiffness of a mechanical oscillator with a digital signal processor, low frequency inputs are projected onto a higher resonance frequency, thus exploiting the natural selective filtering of such structures.Described is an optimized dual-term nonlinear stiffness resonator that enhances the input signal level and the sensitivity to chang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Recent theoretical analysis for PA include the effects of quadratic and cubic nonlinearities [7], dualfrequency parametric amplifiers with quadratic and cubic nonlinearities [54], regular and chaotic vibrations with time delay [55], and frequency comb responses [56].…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical analysis for PA include the effects of quadratic and cubic nonlinearities [7], dualfrequency parametric amplifiers with quadratic and cubic nonlinearities [54], regular and chaotic vibrations with time delay [55], and frequency comb responses [56].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that for specic positions of the parametric excitation force and real-time topology modication it is possible to amplify specic inputs in a three degree of freedom system. Coupling between the quadratic and cubic nonlinearities with the dual-frequency parametric amplication model of the Dung oscillator was studied in [32]. Moreover, in [33] a combination of two piezoelectric cantilever beams with magnetic tip masses having direct and parametric excitation is introduced as a model of the EH device.…”
Section: Introductionmentioning
confidence: 99%
“…Resonators are commonly excited near primary resonance. However, other excitation methods have been explored recently for various applications [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Parametric excitation near twice the structure's natural frequencies is among the most common. Parametric excitation has been used in various applications including signal amplification [10,11,19], thermo mechanical noise squeezing [12], and RF filtering [13]. Multi or mixed-frequency excitation has been used as well, in which two or more frequency signals are mixed and applied to the resonator [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation